Impact of Divergent Thinking Training on Teenagers’ Emotion and Self-Efficacy During the COVID-19 Pandemic - Zuo, Bin; Wang, Qi; Qiao, Yalan; Ding, Yu; Wen, Fangfang (Frontiers in Psychology, 2021)
Currently due to the COVID-19 pandemic, young people are experiencing a decrease in self-efficacy and an increase in mental illness. Though previous studies have shown that self-efficacy and divergent thinking training are positively related, little is known about the impact of divergent thinking training on self-efficacy and emotions. Therefore, our study seeks this answer to support teenagers injured psychologically during disastrous periods. We randomly assigned 70 students to a 2 (time: pretest, post-test) × 2 (groups: divergent thinking training, controlled) mixed design. Participants in the experimental group were given a 9-day divergent thinking training with the theme of “writing down 10 novel functions of the mask,” while those in the control group spent 10 min each day recording what they ate. The self-efficacy, anxiety, depression, and stress of two groups were measured before and after training. Results showed that, compared to the control group, self-efficacy ceased decreasing while anxiety decreased for the experimental group. These findings confirm the positive effect of divergent thinking on teenagers. Implications and limitations are discussed.